SUSTAINABLE ENVIRONMENTAL MANAGEMENT IN NUSANTARA CAPITAL CITY: LEGAL PERSPECTIVES AND BEST PRACTICES - Ardani, Mira Novana; Yusriyadi, Yusriyadi; Silviana, Ana (Fakultas Hukum, Universitas Diponegoro, 2024)
The establishment of Ibu Kota Nusantara (IKN), Indonesia’s future capital, introduces both challenges and opportunities for sustainable environmental management. Effective spatial planning is essential to balance developmental needs with ecological conservation. This study examines how spatial planning principles can be integrated within IKN’s environmental management framework, addressing key legal issues related to infrastructure development, environmental preservation, and the social and economic impacts of spatial policies. Through a normative legal research methodology, incorporating statutory and conceptual approaches, this paper assesses relevant laws, regulations, and environmental planning practices applicable to IKN. The findings highlight the importance of comprehensive spatial planning, robust legal enforcement, and continuous monitoring for long-term sustainability. The study argues that embedding spatial planning in policy-making is critical to mitigating environmental impacts, strengthening community resilience, and supporting sustainable development goals for Nusantara Capital City.